2010
DOI: 10.1371/journal.pone.0013436
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Costs Due to Ocean Acidification Drives Phytoplankton to Be More Heavily Calcified: Optimal Growth Strategy of Coccolithophores

Abstract: Ocean acidification is potentially one of the greatest threats to marine ecosystems and global carbon cycling. Amongst calcifying organisms, coccolithophores have received special attention because their calcite precipitation plays a significant role in alkalinity flux to the deep ocean (i.e., inorganic carbon pump). Currently, empirical effort is devoted to evaluating the plastic responses to acidification, but evolutionary considerations are missing from this approach. We thus constructed an optimality model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
2
14
1
Order By: Relevance
“…At the level of the organism, modelling by Irie et al (2010) suggested that an increase in coccolith mass (as reported by several but not all investigators: see above and Fukuda et al 2011, Krug et al 2011, Langer 2011, Richier et al 2011) was, counter-intuitively, the optimal evolutionary response to decreasing ocean CO 3 2− . It must be emphasised that this conclusion rests on the untested assumption that increased mass decreases mortality.…”
Section: ↓(↑): Decrease (Increase);mentioning
confidence: 83%
“…At the level of the organism, modelling by Irie et al (2010) suggested that an increase in coccolith mass (as reported by several but not all investigators: see above and Fukuda et al 2011, Krug et al 2011, Langer 2011, Richier et al 2011) was, counter-intuitively, the optimal evolutionary response to decreasing ocean CO 3 2− . It must be emphasised that this conclusion rests on the untested assumption that increased mass decreases mortality.…”
Section: ↓(↑): Decrease (Increase);mentioning
confidence: 83%
“…Elevated CO 2 increases the costs of calcification (Irie et al 2010, Raven 2011, Raven & Crawfurd 2012, thereby lowering available energy and reducing calcification at low light levels.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased calcification rate under OA is partially caused by increasing energy costs of calcification (Irie et al 2010, Raven 2011, Raven & Crawfurd 2012, which is required to sustain a sufficient supply of CO 3 2− in the coccolith-forming vesicle, and net H + efflux (Raven 2011). Therefore, based on the documented knowledge on the effects of OA and/or light intensity on E. huxleyi, we hypothesize that increased levels of supplied energy with high levels of solar radiation may offset the negative effects of OA on calcification of E. huxleyi.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean acidification makes calcification more difficult, but increased pCO 2 appears to facilitate primary production for this group with variable outcome for the growth success of the species (Zondervan 2007, Iglesias-Rodriguez et al 2008, Bach et al 2011). Inclusion of other factors for an evaluation of the competitiveness of coccolithophores in the future ocean (Irie et al 2010, Xu et al 2011 makes predictions even less robust at present. The degree of water column stability exerts an additional strong selective pressure on phytoplankton composition (Falkowski & Oliver 2007).…”
Section: Role Of Phytoplanktonmentioning
confidence: 99%